E-Cigarettes and Pregnancy. Is a Closer Look Appropriate?. Issue 2 (June 2016) - Bryce, R.; Robson, S.J.
Abstract : ( Aust N Z J Obstet Gynaecol . 2015;55(3):218–221) It has been estimated that 1 of every 7 pregnant women in Australia smokes, and the trend does not appear to be decreasing. As smoking is one of the most avoidable causes of a variety of adverse outcomes in pregnancy, it is important to encourage women to quit smoking as early as possible.